Hi,
How would l go about re-arranging the following equation to find L?
X = FL^3/3EI
Thanks in advance.
Not sure if this is really what you are asking, but I am taking each of $\displaystyle X,F,E,L,I\in \mathbb{R}$ just variables in some equation. Note $\displaystyle E,I\not = 0$ or else you get division by 0.
$\displaystyle X = \frac{FL^3}{3EI}$
$\displaystyle 3XEI= FL^3$
$\displaystyle \frac{3XEI}{F}= L^3$
$\displaystyle (\frac{3XEI}{F})^{1/3}= L$
If $\displaystyle F=0$ you get $\displaystyle X=0$ and $\displaystyle L$ could be anything.